Applications of Big Data and Artificial Intelligence in Smart Energy Systems Volume 1 Smart Energy System: Design and Its State-Of-the Art Technologies. - Nagpal, Neelu; Alhelou, Hassan Haes, 1988-; Siano, Pierluigi; Sanjeevikumar, Padmanaban, 1978-; Lakshmi, D. (River Publishers Series in Computing and Information Science and Technology Series., 2023)
This book covers the applications of various big data analytics, artificial intelligence, and machine learning technologies in smart grids for demand prediction, decision-making processes, policy, and energy management.